Emendation of autophagic dysfuction in neurological disorders: a potential therapeutic target. (4th May 2022) - Sainani, Shivani R.; Pansare, Prajakta A.; Rode, Ketki; Bhalchim, Vrushali; Doke, Rohit; Desai, Shivani
Abstract: Background: Neurological disorders have been continuously contributing to the global disease burden and affect millions of people worldwide. Researchers strive hard to extract out the ultimate cure and serve for the betterment of the society, and yet the treatments available provide only symptomatic relief. Aging and abnormal mutations seem to be the major culprits responsible for neurotoxicity and neuronal death. One of the major causes of these neurological disorders that has been paid utmost attention recently, is Autophagic Dysfunction. Aim: The aim of the study was to understand the autophagic process, its impairment in neurological disorders and targeting the impairments as a therapeutic option for the said disorders. Methods: For the purpose of review, we carried out an extensive literature study to excerpt the series of steps involved in autophagy and to understand the mechanism of autophagic impairment occurring in a range of neurodegenerative and neuropsychiatric disorders like Parkinson, Alzheimer, Depression, Schizophrenia, Autism etc. The review also involved the exploration of certain molecules that can help in triggering the compromised autophagic members. Results: We found that, a number of genes, proteins, receptors and transcription factors interplay to bring about autophagy and plethora of neurological disorders are associated with the diminished expression of one or more autophagic member leading to inhibition of autophagy. Conclusion: Autophagy is a significant process for the removal of misfolded, abnormal, damaged protein aggregates and nonfunctional cell organelles in order to suppress neurodegeneration. Therefore, triggering autophagy could serve as an important therapeutic target to treat neurological disorders.